Understanding bereavement experiences of mothers facing the loss of newborn infants - Larissa Rodrigues; Daniela Danttas Lima; Juliana Vasconcelos Freitas de Jesus; Gabriel Lavorato Neto; Egberto Ribeiro Turato; Claudinei José Gomes Campos (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objective: to understand mothers' bereavement experiences regarding the loss of their newborn child in the Neonatal Intensive Care Unit of a Brazilian university hospital. Methods: the study was designed by the clinical-qualitative method to understand the meaning of the emerging relationships of health scenarios. Sample consisted of six mothers. The sufficiency of the sample was verified through the saturation of the data. The data collection instrument was a semistructured interview with script of open questions, the collected material was recorded and transcribed in full. Thematic analysis was performed by two independent authors. Results: feelings and perceptions of the grieving process gave rise to three categories: 1. Guilt and fantasy of bereavement related to the death and grief for their children; 2. Relationships and ambiguities - the relationship between internal concerns and perception of external relations; 3. Fear, disbelief, abandonment and loneliness - questions about perception of the external environment. Conclusions: mothers' bereavement experience is mainly permeated by loneliness and abandonment related to feelings of guilt for not being able to keep their children alive. The difficult and definitive separation in the postpartum period, caused by death, brings fantasies of reunion with their child. Women show the need to realize grief, especially by recognizing their baby's identity.